Axonal debris accumulates in corneal epithelial cells after intraepithelial corneal nerves are damaged: A focused Ion Beam Scanning Electron Microscopy (FIB-SEM) study. (May 2020) - Parlanti, Paola; Pal-Ghosh, Sonali; Williams, Alexa; Tadvalkar, Gauri; Popratiloff, Anastas; Stepp, Mary Ann
Abstract: The intraepithelial corneal nerves (ICNs) that innervate the corneal epithelium are maintained through interactions with corneal epithelial cells and the extracellular matrix they produce. One to several axons bundle together within the basal cell layer and extend parallel to the ocular surface or branch and extend apically. Here we use 3-dimentional (3D) ultrastructural reconstructions of control and trephine injured mouse corneal epithelium and stroma produced using Focused Ion Beam Scanning Electron Microscope (FIB-SEM) to determine whether corneal epithelial or immune cells resident in the epithelium remove axonal debris and degrade it in their lysosomes after trephine injury to the cornea. We demonstrate that axonal fragments are internalized in the corneal epithelium and accumulate within electron dense structures consistent with lysosomes 3 h after trephine injury in both epithelial and immune cells located among the basal cells of the trephine injured cornea. Confocal imaging showed fewer CD45 + immune cells within the corneal epithelium after trephine injury compared to controls. The resolution obtained using FIB-SEM also allowed us to show that the presence of sensory axons at the basal aspect of the epithelial basal cells close to the anterior aspect of the epithelial basement membrane (EBM) is associated with a focal reduction in EBM thickness. In addition, we show using FIB-SEM and confocal imaging that superficial trephine injuries that do not penetrate the stroma, damage the integrity of anterior stromal nerves. These studies are the first to look at the mouse cornea following nerve injury using FIB-SEM. Graphical abstract: Image 1 Highlights (each bullet no more than 85 characters including spaces): FIB-SEM shows the EBM thinning near sites where ICNs come in close contact. FIB-SEM shows debris in lysosomes after trephine injury. Stromal nerves impacted by trephine only injury. Immune cells are reduced at the corneal periphery after trephine injury.